PENGUATAN LITERASI SISWA SMA MELALUI PENULISAN FEATURE BERBASIS KISAH HIDUP NARASUMBER DALAM LOMBA MENULIS DI KABUPATEN TTU - Kristophorus Ukat; Anselmus Yata Mones; Marianus Sesfao (LPPM STP St. Petrus Keuskupan Atambua, 2026)
Abstract: This study examines the implementation of an experiential-based literacy program through a feature writing competition aimed at strengthening students’ literacy skills in North Central Timor Regency. The program was carried out through several stages, including perception alignment, school-based mentoring, writing practice, and evaluation and reflection on the outcomes. The study employed data triangulation through observation, interviews, and analysis of students’ written works. The findings indicate that the experiential learning approach increased students’ engagement, particularly in the affective and reflective dimensions, and supported the development of narrative ideas. However, the study also identified a gap between students’ storytelling abilities and their mastery of journalistic writing techniques, including weaknesses in language use. Nevertheless, the program had a positive impact on students’ self-confidence, motivation, and reflective awareness. The study concludes that experience-based literacy is effective as an entry point for developing contextual literacy. However, this approach still requires continuous reinforcement in technical writing skills and students’ linguistic competence. Key Words: Experiential learning, Literacy, Feature writing, Narrative competence, Contextual literacy Abstrak: Penelitian ini mengkaji implementasi program literasi berbasis pengalaman melalui lomba penulisan feature untuk memperkuat kemampuan literasi siswa di Kabupaten Timor Tengah Utara. Program dilaksanakan melalui beberapa tahap, yaitu penyamaan persepsi, pendampingan di sekolah, praktik menulis, serta evaluasi dan refleksi hasil. Penelitian menggunakan triangulasi data melalui observasi, wawancara, dan analisis karya siswa. Hasil penelitian menunjukkan bahwa pendekatan experiential learning meningkatkan keterlibatan siswa, terutama pada aspek afektif dan reflektif, serta membantu pengembangan ide naratif. Namun, masih ditemukan kesenjangan antara kemampuan bercerita dan penguasaan teknik jurnalistik, termasuk kelemahan pada aspek kebahasaan. Meski demikian, kegiatan ini memberikan dampak positif terhadap peningkatan kepercayaan diri, motivasi, dan kesadaran reflektif siswa. Penelitian menyimpulkan bahwa literasi berbasis pengalaman efektif sebagai sarana pengembangan literasi kontekstual. Akan tetapi, pendekatan ini tetap memerlukan penguatan berkelanjutan pada kemampuan teknis penulisan dan kompetensi kebahasaan siswa. Kata Kunci: experiential learning, literasi, penulisan feature, kompetensi naratif, literasi kontekstual